Flexural behaviour of profiled steel decking using finite element analysis - Muhammad Azim Shafiq, Mohd Zulhairi (2019)
Finite element is widely used nowadays especially towards civil engineering field. Profiled steel decking has been used as part of composite slabs design where the steel deck is utilized as permanent form work and tensile reinforcement for composite slabs. This study aims to focus the response of bare profiled steel deck with a present of c-channel in unpropped construction. Nine specimen of four-point bending test will be model in Abaqus to investigate the response of profiled steel deck at various spans. Three set of specimen consists of strengthen with c-channel and unstrengthen with c-channel. Result from this study show that a profiled steel deck strengthen with c-channel more efficient than unstrengthen with c-channel. The findings from this study will be used to make recommendations for design engineers.